Dry powder nasal drug delivery: challenges, opportunities and a study of the commercial Teijin Puvlizer Rhinocort device and formulation. (2nd October 2016) - Pozzoli, Michele; Rogueda, Philippe; Zhu, Bing; Smith, Timothy; Young, Paul M.; Traini, Daniela; Sonvico, Fabio
Abstract: Purpose: To discuss the challenges and opportunities for dry powder nasal medications and to put this in to perspective by evaluating and characterizing the performance of the Teijin beclomethasone dipropionate (BDP) dry powder nasal inhaler; providing a baseline for future nasal products development. Methods: The aerosol properties of the formulation and product performance of Teijin powder intranasal spray were assessed, with a particular focus on particle size distribution (laser diffraction), powder formulation composition (confocal Raman microscope) and aerosol performance data (British Pharmacopeia Apparatus E cascade impactor, aerosol laser diffraction). Results: Teijin Rhinocort ® (BDP) dry powder spray formulation is a simple blend of one active ingredient, BDP with hydroxypropylcellulose (HPC) carrier particles and a smaller quantity of lubricants (stearic acid and magnesium stearate). The properties of the blend are mainly those of the carrier ( D v50  =  98 ± 1.3 µm). Almost the totality of the capsule fill weight (96.5%) was emitted with eight actuations of the device. Using the pharmacopeia suggested nasal chamber deposition apparatus attached to an Apparatus E impactor. The BDP main site of deposition was found to be in the nasal expansion chamber (90.2 ± 4.78%), while 4.64 ± 1.38% of the BDP emitted dose was deposited on Stage 1 of the Apparatus E. Conclusions: The Teijin powder nasal device is a simple and robust device to deliver pharmaceutical powder to the nasal cavity, thus highlighting the robustness of intranasal powder delivery systems. The large number of actuations needed to deliver the total dose (eight) should be taken in consideration when compared to aqueous sprays (usually two actuations), since this will impact on patient compliance and consequently therapeutic efficacy of the formulation.